WORK MOTIVATION MANAGEMENT IN INCREASING THE EFFECTIVENESS OF EDUCATIONAL INSTITUTIONS - Hamdani, M. Solehuddin Rikza (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to analyze the Management of Work Motivation in Improving the Effectiveness of Educational Institutions at RAM NU As-Sholihi Tekung. This research uses a qualitative case study type approach. Data collection techniques using interviews, observation and documentation. The data analysis was carried out in stages, starting with data collection, data reduction and drawing conclusions. The results showed that there was a correlation between applying work motivation and increasing institutional effectiveness, as evidenced by the existence of new and old programs that continued to run effectively with support and cooperation. all educators and service users.